Multifield-resolved phonon spectrometrics: structured crystals and liquids. (September 2019) - Yang, Xuexian; Peng, Chang; Li, Lei; Bo, Maoling; Sun, Yi; Huang, Yongli; Sun, Chang Q.
Abstract: Bond relaxation from one equilibrium to another under perturbation matters uniquely the performance of a substance and thus it has enormous impact to materials science and engineering. However, the basic rules for the perturbation-bond-property correlation and efficient probing strategies for high-resolution detection stay yet great challenge. This treatise features recent progress in this regard with focus on the multifield bond oscillation notion and the theory-enabled phonon spectrometrics. From the perspective of Fourier transformation and the Taylor series of the potentials, we correlate the phonon spectral signatures directly to the transition of the characteristic bonds in terms of stiffness (frequency shift), number fraction (integral of the differential spectral peak), structure fluctuation (linewidth), and the macroscopic properties of the substance. A systematic examination of the spectral feature evolution for group IV, III-V, II-VI crystals, layered graphene nanoribbons, black phosphor, (W, Mo)(S2, Se2 ) flakes, typical nanocrystals, and liquid water and aqueous solutions under perturbation has enabled the ever-unexpected information on the perturbation-bond-property regulations. Consistency between predictions and measurements of the crystal size-resolved phonon frequency shift clarifies that atomic dimer oscillation dictates the vibration modes showing blueshift while the collective vibration of oscillators formed between a certain atom and its nearest neighbors governs the modes of redshift when the sample size is reduced. Theoretical matching to the phonon frequency shift due to atomic undercoordination, mechanical and thermal activation, and aqueous charge injection by solvation has been realized. The reproduction of experimental measurements has turned out quantitative information of bond length, bond energy, single bond force constant, binding energy density, vibration mode activation energy, Debye temperature, elastic modulus, and the number and stiffness transition of bonds from the mode of references to the conditioned upon perturbation. Findings prove not only the essentiality of the multifield lattice oscillating dynamics but also the immense power of the phonon spectrometrics in revealing the bond-phonon-property correlation of solid and liquid substance. Graphical abstract: Image 1 Highlights: Development of regulations for the multifield bond oscillation dynamics and energetics. Bond vibration frequencies vary with programmed perturbation of the crystal potentials. Frequency shift correlates the perturbation-relaxation-property of a substance. Phonon spectrometrics offers ever-unexpected information on the performance of bonds. Abstract : Atomic undercoordination, charge injection, mechanical and thermal activation mediate material's properties intrinsically by bond relaxation from one equilibrium to another while the phonon spectrometrics probes the ever-unexpected information of the binding energy density, atomic cohesive energy, single bond force constant, crystal elastic modulus, Debye temperature and the abundance-length-stiffness transition of bonds under perturbation Key Points treated as abstract teaser kindly check and correct if necessary.-->.